Economic reforms in Poland - Hubert Gabrisch (Intereconomics, 1981)
The reaction of the Polish leadership to the strikes in August 1980 was to promise reforms, and a scheme of reforms has been presented in the meantime. What would be the most comprehensive attempt yet at transforming the present system, which is geared to the Soviet model, and at launching the country on a road of its own is to be undertaken by 1983. What are the prospects for this new reform scheme?
Keywords: 330; Eastern Europe